Gandhi - Attenborough, Richard; Briley, John.; Kingsley, Ben.; Bergen, Candice, 1946-; Fox, Edward, 1937-; Gielgud, John, 1904-2000.; Howard, Trevor, 1916-1988.; Mills, John, 1908-2005.; Sheen, Martin; Williams, Billy; Taylor, Ronnie; Shankar, Ravi, 1920-2012.; et al. (Burbank, CA : Columbia TriStar Home Video, 2001)
Tells the story of Gandhi's adult life, when he led an entire country to freedom, using non-violent methods.
Originally released as a motion picture in 1982.
Special features include: Ben Kingsley talks about Gandhi; original newsreel footage of Gandhi in England, his farewell talk in Europe, and the Mahatma Gandhi death fast; the making of Gandhi photo montage ; the works of Mahatma Gandhi; filmographies; theatrical trailer.
Directors of photography, Billy Williams, Ronnie Taylor ; editor, John Bloom ; music, Ravi Shankar, George Fenton.
Ben Kingsley, Candice Bergen, Edward Fox, John Gielgud, Trevor Howard, John Mills, Martin Sheen.
MPAA rating: PG.
DVD, Region 1, widescreen presentation (aspect ratio 2.35:1); Dolby Digital 5.1.
Keywords: Gandhi, -- Mahatma, -- 1869-1948 -- Drama; Gandhi, -- Mahatma, -- 1869-1948 -- Teatro; Gandhi, -- Mahatma, -- 1869-1948; 1919 - 1947; Nonviolence -- Drama; Nonviolence; Political science; Race relations; India -- Politics and government -- 1919-1947 -- Drama; South Africa -- Race relations -- Drama; India -- Gobierno -- 1919-1947 -- Teatro; India -- y -- idex9; 7.150.; India; South Africa; Feature films; Biographical films; Films for the hearing impaired; Biographical films; Drama; Feature films; Films -- for the hearing impaired